(untitled) (Journal of Management and Business Education, 2020)
Recent studies show that the use of self-assessment activities is a key learning mechanism, since they provide an important feedback that increases students’ motivation promoting greater responsibility on their own learning. Similarly, the evidence indicates that the use of gamification tools improves students’ extrinsic and intrinsic motivation. Combining these two approaches, this paper analyzes the role played by self-assessments activities performed using the Kahoot gamification tool and its impact on students’ learning process and outcomes –considering academic’s success and performance rates. Additionally, the gender has been considered in terms of its moderating effect on these relationships. Our findings indicate that students who have carried out self-assessment activities through Kahoot achieve higher success and performance rates compared to those students who have not. Moreover, we find that students’ gender moderates the relationship between the use of Kahoot and their academic performance.